Issues of Improving the Audit of Financial Statements in Winery Industry Enterprises - Botirov, L. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article highlights the importance of conducting audits of financial statements and the practical application of audit procedures used to obtain audit evidence in the audit of financial statements. During the audit, proposals and recommendations were developed by independent auditors regarding the sequence of audit actions that should be used in client enterprises, as well as the elimination of problems in their application.